Jim Dinsmore letter to Thomas Kent regarding additional bird information, March 4, 1981 - Dinsmore, James J.et al (1981)
This letter updates the Jim Dinsmore report on the raptor survey for Story and Boone Counties and also includes additional sightings by Jim Dinsmore and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed